FR2.2: A systems approach to sustainable and inclusive farmer-led irrigation development: A case analysis from Nepal - Uprety, Labisha; Khadka, Manohara; Shrestha, Gitta; Minh, Thai Thi; Schmitter, Petra S. (International Water Management Institute, 2022)
Farmer-led irrigation development (FLID) in Nepal has been largely synonymous to farmer-managed surface irrigation, rather than a broader encompassing of all farmer-led decisions, including small-scale choices. Many of the elements that affect farmer's adoption of social, technological, or institutional innovations in irrigation and agriculture are interconnected and need to be systemically examined to present a thorough analysis. This paper thereby presents a systemic analysis to better understand opportunities and barriers to farmer-led irrigation development in Nepal, especially for smallholders and women farmers. This is done by characterizing systemic barriers and opportunities shaped by policy environments, agricultural value chains, irrigation supply chains, private-public interventions, gender equality and social inclusion, (GESI) and new drivers such as COVID-19. The focus is on their intrinsic connections and mapping the ecosystem in which FLID is embedded. This paper is based on extensive qualitative literature and policy review coupled with primary data obtained through telephone interviews on analysing socio-economic policies, institutions, markets, and GESI-related barriers and opportunities in Nepal. The outcome is a comprehensive framework for sustainable and inclusive FLID.